Encephalocraniocutaneous Lipomatosis. Issue 7 (October 2018) - Bavle, Abhishek; Shah, Rikin; Gross, Naina; Gavula, Theresa; Ruiz-Elizalde, Alejandro; Wierenga, Klaas; McNall-Knapp, Rene
Abstract : A 5-year-old boy presented with worsening headaches for 3 months. On examination, he was found to have a hairless fatty tissue nevus of the scalp (nevus psiloliparus), subcutaneous soft tissue masses on the right side of his face, neck, mandible and right buttock and epibulbar dermoid of the right eye (choristoma) (Figs. 1A, B ). Magnetic resonance imaging revealed a large suprasellar mass, which was debulked and found to be a pilocytic astrocytoma. Testing was not performed for the BRAF/KIAA1549 fusion or BRAFV600E mutation. Seven years later, he was started on adjuvant chemotherapy for gradual tumor progression. Over the ensuing 3 years, he had further disease progression despite treatment with 3 frontline chemotherapy regimens: vinblastine, carboplatin/vincristine, and irinotecan/bevacizumab. Targeted sequencing of tissue from the right gluteal mass, revealed a mosaic activating FGFR1 c.1966A>G (p.Lys656Glu) mutation, absent in normal left gluteal tissue, confirming the diagnosis of encephalocraniocutaneous lipomatosis (ECCL), belonging to the family of RASopathies (including neurofibromatosis type I, Noonan syndrome, Costello syndrome), with constitutive activation of the mitogen-activated protein kinase (MAPK) pathway, and an increased risk of developing neoplasms. He was started on trametinib, a MEK inhibitor, off-label, targeting the MAPK pathway downstream from FGFR1, with stable tumor size at last follow-up, after 6 months on therapy.